Persepsi Mahasiswa Terhadap Isu Kesetaraan Gender di Lingkungan Kampus UIN Suska Riau - Annur Rosida Siregar; Mita Andira; Muhammad Reza; Nanda Lubis; Tsaniyah Andhini; Sukma Erni (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Gender equality is a condition where men and women are equal in fulfilling rights and policies. Gender equality is related to equal pay in work, zero tolerance for sexual harassment, equal opportunities in education, both men and women get the same position in work. Gender equality is also related to socialist feminist theory, where the thinking is related to the sharpening of oppression in the capitalist and patriarchal systems which cause social oppression. The aim of this research is to determine the perceptions of students at the Sultan Syarif Kasim Riau Islamic University regarding the issue of gender equality in education. The method used is a qualitative. The data collection techniques used were questionnaires, interviews, literature. The results of this research indicate that students at the Sultan Syarif Kasim Riau Islamic University are in the circle of gender equality in education.